Life Cycle Assessment of Production Bio-oil from Thermal Cracking Empty Fruit Bunch (EFB) - Daya Wulandari; Rusdianasari Rusdianasari; Muhammad Yerizam (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Empty fruit bunch (EFB) is one of the abundant biomass waste from oil palm and it is an issue that it can be used as renewable energy in the form of Bio-oil. Bio-oil is produced by a thermal cracking process. This research aims to identify the potential environmental impact of Bio-oil production from EFB as fuel. Life Cycle Assessment (LCA) with gate to gate approach is used in data processing applications for networks in Simapro V.9 and the database used is similar to the characteristics of the eco invent database. Functional units are used to show environmental references in impact categories, such as energy used and global warming potency. The results show that the stage of the bio-oil production cycle in the pretreatment process has a greater global warming impact than the others, amounting to 131.10013 kg CO2 eq. The results of the analysis using the networking graph on the Simapri, show that the environmental hotspot of the thermal cracking process for Bio-oil production is caused by the use of electricity from the State Electricity Company (PLN) and the release of chemical substances from the process. From the results of the LCA, environmental performance improvement or continuous improvement can be done is by managing energy use and installing equipment.